2018
DOI: 10.1109/tnet.2018.2873606
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Policies for Minimizing Age of Information in Broadcast Wireless Networks

Abstract: We consider a wireless broadcast network with a base station sending time-sensitive information to a number of clients through unreliable channels. The Age of Information (AoI), namely the amount of time that elapsed since the most recently delivered packet was generated, captures the freshness of the information. We formulate a discrete-time decision problem to find a transmission scheduling policy that minimizes the expected weighted sum AoI of the clients in the network.We first show that in symmetric netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
436
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(447 citation statements)
references
References 50 publications
11
436
0
Order By: Relevance
“…When there is no packet-loss in the network, this greedy policy is equivalent to the round robin strategy, which is shown to be order optimal when update packets can not be generated at will and arrive randomly [24]. In [18], it is revealed that users with relatively bad channel states are updated less frequently. Scheduling in networks with timevarying channels are studied in [20], [21], where channels with two states is considered, and centralized and decentralized policies to minimize AoI are proposed respectively.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…When there is no packet-loss in the network, this greedy policy is equivalent to the round robin strategy, which is shown to be order optimal when update packets can not be generated at will and arrive randomly [24]. In [18], it is revealed that users with relatively bad channel states are updated less frequently. Scheduling in networks with timevarying channels are studied in [20], [21], where channels with two states is considered, and centralized and decentralized policies to minimize AoI are proposed respectively.…”
Section: Related Workmentioning
confidence: 99%
“…The constraint Eq. (19b)-(19d) can be obtained by substituting ξ x,q with y x,q and µ x,q with relationship (18). Notice that ξ x,q ≤ 1, the inequality constraint (19e) can be obtained.…”
Section: Probabilistic Scheduling Policy For Single Sensor Casementioning
confidence: 99%
See 1 more Smart Citation
“…Next, we optimize parameter θ to reduce the right-hand side of (17). Note that scheme (18) always minimizes the right-hand side of (17), and the stationary randomized scheme that independently updates with probability ρ at each time slot is also a feasible scheme. Substituting the stationary randomized scheme into the right-hand side of (17) yields…”
Section: B Status Updating Schemementioning
confidence: 99%
“…Aside from the conventional throughput QoS considera-arXiv:1903.02242v1 [cs.IT] 6 Mar 2019 tion [4], various types of latency metrics are among the main concerns. For example, the recently proposed AoI [5] can be regarded as a metric for information delay; a line of work [2], [3], [6], [7] has been focused on optimizing AoI in wireless multi-access (or broadcast) networks wherein Whittle's index was used to capture the transmission urgency of terminals. Conventional packet delay metric was widely investigated in the literature and various scheduling policies for multi-access networks have been proposed, most evidently in [8].…”
Section: A Related Workmentioning
confidence: 99%